Large-scale nanometer-thickness graphite films synthesized on polycrystalline Ni foils by two-stage chemical vapor deposition process. (March 2017) - Hu, Qicheng; Kim, Seul-Gi; Shin, Dong-Wook; Kim, Tae-Sung; Nam, Ki-Bong; Kim, Mun Ja; Chun, Hwan-Chul; Yoo, Ji-Beom
Abstract: In this work, large-scale (120 × 120 mm) nanometer-thick graphite films (NGFs) were synthesized on polycrystalline Ni foils using a "two-stage" chemical vapor deposition (CVD) process. An intermediate cooling process was included in the CVD process; this process affected the isothermal graphene growth, which is explained using a growth model. We mainly studied a graphite film with the thickness of ∼40 nm and the good thickness uniformity was characterized by atomic force microscopy (AFM), Raman spectroscopy and extreme ultraviolet (EUV) mapping. The graphite formed on the Ni grain boundary was analyzed by transmission electron microscopy (TEM). The relationships between the thickness, optical and electrical properties of the NGF and growth temperature were also studied. Graphical abstract: